The Effects of Trainings with Futsal Ball on Dribbling and Passing Skills on Youth Soccer Players - ERDEM, KAMİL (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2018)
The aim of this study is to examine the effect of futsal balls on the passing and dribbling skills of 11-12 year old of soccer players. For this purpose, 48 male students whom regularly went to soccer school participated in the study. 24 of the students were in the control group (CG) and the other 24 were in the experimental group (EG). While the experimental group exercised with a futsal ball, the athletes in the control group continued their classical training program with a soccer ball. Experimental and control groups were planned to have a total of 24 sessions for 8 weeks, with 3 training sessions per week. The Mor-Christian General Soccer Ability Skill Test Battery (dribbling and passing) was used in the research. Statistical analyses were performed using the SPSS Windows 16.0 package program for the evaluation of the findings obtained in the study. Study results show that while both groups showed statistical improvement in passing skill in the pre and post tests (p<0,05), there wasn't seen any improvement in dribbling skill (p>0,05). However when we compared the improvements between groups, it was seen that EG players improved their passing skills better than CG players (p<0,05). In conclusion, it can be observed that the children who train with heavier and less bouncy futsal balls make contact with the ball more often and they become more focused, which results in an enhacement in their game skills and also has a positive effect on traditional soccer game.
Keywords: Soccer; Adolescent; Passing; Dribbling; INSTEP KICKING; DYNAMICS; COORDINATION; EXPERIENCE; ABILITY